Secondary Glaucoma After Blunt Ocular Trauma - Ega Sekartika; Priya Taufiq Arrachman; Mutia Khanza; Dewi Rosarina (Vision Science and Eye Health Journal, 2022)
Introduction: Ocular trauma is an important cause of unilateral visual impairment and blindness. Among several agents of ocular trauma, blunt trauma is the most common and can lead to secondary glaucoma. Secondary glaucoma due to blunt ocular trauma can be unnoticed and undetected until the formation of glaucomatous optic neuropathy (GON) occurs. This case might not be neglected. Delay in treatment can lead to the progression of GON. Case Presentation: A 68-year-old woman presented to the outpatient clinic in Undaan Eye Hospital complaining of decreased vision and pain in the left eye after blunt trauma to the eye. Her left eye vision was limited to detecting hand motions (1/300) and the intraocular pressure (IOP) was 37.8 mmHg. On the slit lamp biomicroscopic examination, the left pupil was mid-dilated, lens opacification and phacodenesis were detected. The cup-to-disc ratio (CDR) of the left eye increased (0.8-0.9) through the funduscopic examination. Secondary glaucoma due to subluxated lens was diagnosed for the left eye. The patient was given topical and oral antiglaucoma medications and was evaluated after one week of drug use. Since the IOP remained elevated after medical therapy, left eye trabeculectomy was conducted. Bleb was formed postoperatively and the IOP was getting normal without oral glaucoma medications. Conclusion: Blunt ocular trauma can lead to secondary glaucoma. Thorough examinations and immediate treatments should be conducted to preserve patient’s vision and prevent further optic nerve damage.